2016
DOI: 10.20960/nh.769
|View full text |Cite
|
Sign up to set email alerts
|

The NutriQoL ® questionnaire for assessing health-related quality of life (HRQoL) in patients with home enteral nutrition (HEN): validation and fi rst results

Abstract: NutriQoL® is valid, reliable, even if lowly sensitive to change, and useful to measure HRQoL in this population. More studies are needed to know HRQoL in routine practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 0 publications
3
27
0
2
Order By: Relevance
“…This questionnaire, NutriQoL®, consists of 17 items and evaluates QoL in two dimensions (physical performance, daily life activities, and social aspects). This questionnaire is reported to be valid, reliable and even if lowly sensitive to change it seems to be useful to measure QoL in this population [148,149].…”
Section: Grade Of Recommendation Gpp E Strong Consensus (92% Agreement)mentioning
confidence: 96%
“…This questionnaire, NutriQoL®, consists of 17 items and evaluates QoL in two dimensions (physical performance, daily life activities, and social aspects). This questionnaire is reported to be valid, reliable and even if lowly sensitive to change it seems to be useful to measure QoL in this population [148,149].…”
Section: Grade Of Recommendation Gpp E Strong Consensus (92% Agreement)mentioning
confidence: 96%
“…The settings where the studies included took place varied from the community such as HEN to acute hospitals [2,43,45] and these different settings may also influence the impact of enteral tube feeding on patients’ QoL. Methods of enteral feeding could be in the form of bolus, gravity and the use of stationary or mobile enteral feeding pumps and each of these enteral feeding methods have their advantages and drawbacks in terms of how they impact patients’ QoL [46]. For example, the long hours spent by patients who are connected to enteral feed/pump may affect family life, social activities and QoL [47] and the use of mobile pumps and carry bags are possible strategies for ameliorating these challenges.…”
Section: Discussionmentioning
confidence: 99%
“…The authors noted that these generic tools were not sensitive enough in identifying the effect of enteral tube feeding on patients’ QoL. Based on the process used in developing and validating the NutriQoL questionnaire, it was concluded that this measurement tool is valid, reliable and useful instrument for assessing the QoL of patients on HEN irrespective of the disease and/or the route of administration [46,49].…”
Section: Discussionmentioning
confidence: 99%
“…The main objective of this study was to evaluate the QoL in patients receiving HEN, independent of their underlying disease and route of administration, through the validated NutriQoL questionnaire 5 to identify groups of risk whose QoL associated with HEN is more compromised, and, therefore, should receive special attention.…”
Section: Introductionmentioning
confidence: 99%